Industry 4.0 – The Global Industrial Revolution: Achievements, Obstacles and Research Needs for the Digital Transformation of Industry (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue delves into the strides made, challenges encountered, and research imperatives within the realm of Industrie 4.0 from both a scientific and practical standpoint. This publication features the voices of Industrie 4.0 pioneers Henning Kagermann and Wolfgang Wahlster, as well as leaders in research and industrial application of smart manufacturing concepts.